Examination of Predictors for Discharge Disposition in Patients Aged 60 Years or Older with Acute Exacerbation of Heart Failure - TAKAHASHI, Ren; YOKOTA, Junichi; MATSUKAWA, Yuko; MATSUSHIMA, Keisuke (Physical Therapy Japan, 2021)
Objective: To clarify the independent predictors of home discharge in patients with acute exacerbation of heart failure (HF) who underwent cardiac rehabilitation (CR).Methods: This was a single-center retrospective cohort study. In this study, 305 patients aged 60 years or older, who were admitted with acute exacerbation of HF, were included in the analysis. The patients were divided into a Home group and Non-Home group based on discharge disposition. Basic characteristics, HF severity, knee extension strength (KES), Short Physical Performance Battery (SPPB) and Barthel Index (BI) at the commencement of rehabilitation and at hospital discharge were compared between groups. Additionally, multivariate logistic regression analysis and a receiver operating characteristic curve were used to evaluate independent predictors of home discharge and cut-off value.Results: At the commencement of CR, KES, SPPB, and BI were significantly higher and age was significantly lower in the Home group. However, there were no significant differences in HF severity and nutritional status between the groups. At hospital discharge, KES, SPPB, and BI were significantly higher in the Home group. Multivariate analysis showed that predictors of home discharge and its cut-off value were KES at the commencement of CR (≥12.1 kg), SPPB at the commencement of CR (3/4 points), and BI at hospital discharge (≥80 points).Conclusion: These results may contribute to the early detection of older patients who may be difficult to discharge to home and to setting appropriate CR goals.